Gene Mutation Analysis -Role of Open Source Tools for Personalized Medication and Designer Drugs in a Cost-Effective and Efficient Manner - Singh, Tarun Preet (My University, 2014)
We have established Gene Mutation Analysis platform of software pipelines using Open Sources tools (BWA, GATK, Bioconductor, Samtools, VarScan2) on Linux based Operating System. We have implemented GATK best practices for mutation detection. Also, developed browser-based tools for visual analysis of the gene mutations using Open Source tools (JBrowse, HTML5, Javascript, Python). Browser-based visual tool enables clinicians to look atupstream/downstream of the mutation/SNP. The visual tool enables identification of mutation hot-spots, driver mutations and passenger mutation. Quality Checks are made part of the software tools for minimizing possible false-positive detection of gene mutation/SNP. The quality checks based on minimum coverage, Phred scores, ratio of supporting variant and reference alleles. Mutations are further validated using COSMIC, HapMap, Geome Wide Association Studies and clinically flagged SNPs from dbSNP. With help of the above platform and visual tools, the Oncologist is now able to do a triage – look at a patient, look at their lab results and look at their genetic profile visually; they are now able to do more personalized medicine.
ME, CSED
Keywords: Gene Mutation; Personalized Medication; Germline Screening